Ruptured choledochal cyst during early pregnancy with successful fetomaternal outcome. (13th April 2018) - Varun, Neha; Elahi, Arifa Anwar; Gupta, Nidhi; Nigam, Aruna
Abstract : Choledochal cyst is a rare congenital malformation which is usually found in young children and adolescents but can rarely present in the adult age group. It can present with several complications like cholangitis, pancreatitis, biliary cirrhosis, portal hypertension, liver abscess, malignancy and rarely spontaneous rupture (in 2% of cases) causing biliary peritonitis. A case of spontaneous rupture of choledochal cyst during second trimester of pregnancy is reported where the patient was managed by minimal surgery, peritoneal washout, placement of T-tube and planned for definitive treatment in the postpartum period. The pregnancy continued till 35 weeks with favourable fetomaternal outcome.